2019
DOI: 10.1111/ppe.12576
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adverse perinatal outcomes among women with pharmacologically treated and untreated depression during pregnancy: A retrospective cohort study

Abstract: Background The association between antidepressant use during pregnancy and adverse perinatal outcomes is unclear. The association without taking into consideration the independent effect of depression leads to a confounding of the effects of antidepressants with those of the underlying reason for the use of those medications. Additionally, a history of depression and antidepressant use may also influence this association. Objective This study examined the risks of adverse perinatal outcomes associated with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…34 This research group found an independent association with adverse perinatal outcomes for both antidepressant use (70% SSRI) and depression with no antidepressant use. 34 Our research highlights that mood disorder alone may increase the risk for CHD. The impact of substance self-medication, stress and possible pharmacogenetic vulnerabilities needs further investigation in women with a mood disorder.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…34 This research group found an independent association with adverse perinatal outcomes for both antidepressant use (70% SSRI) and depression with no antidepressant use. 34 Our research highlights that mood disorder alone may increase the risk for CHD. The impact of substance self-medication, stress and possible pharmacogenetic vulnerabilities needs further investigation in women with a mood disorder.…”
Section: Discussionmentioning
confidence: 90%
“…Although they did not investigate women with a history of a mood disorder without antidepressant use, they did find an increased prevalence of foetal CHD in a small group of women who used SSRI medication in the year before or after pregnancy but not in the first trimester. This differentiation of data is more clearly investigated by Adhikari and colleagues who highlight the importance and potential impact of the underlying mood disorder on perinatal adverse outcomes separate from antidepressant exposure 34 . This research group found an independent association with adverse perinatal outcomes for both antidepressant use (70% SSRI) and depression with no antidepressant use 34 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The women who discontinue their medication have a higher risk of relapsing during pregnancy compared with women who maintained their antidepressant medication (4,78,82). Discontinuation of antidepressant medication during pregnancy leads to treatment resumption in 12-57% of the cases before childbirth (75,(83)(84)(85). Factors associated with treatment resumption for pregnant women in Sweden are: a greater burden of pre-pregnancy psychiatric illnesses, multipara, higher educational level and have been born in the Nordic countries or the EU.…”
Section: Antidepressant Medication During Pregnancymentioning
confidence: 99%
“…Therefore, even if the exact gestational age when dose changed is unknown, the results will not be biased insofar as women fall into the correct group of women with similar antidepressant use. On the other hand, a more simplified analysis may miss important nuances, as a previous study using a dichotomous definition of antidepressant use with a minimum threshold of adherence throughout pregnancy did not find an association between antidepressant use and maternal morbidity …”
mentioning
confidence: 99%